Effects of Compliance With Procedure-Specific Postoperative Rehabilitation Protocols on Initial Outcomes After Osteochondral and Meniscal Allograft Transplantation in the Knee. Issue 11 (22nd November 2019) - Rucinski, Kylee; Cook, James L.; Crecelius, Cory R.; Stucky, Renée; Stannard, James P.
Background: Osteochondral and meniscal allograft transplantation have been performed in the knee for more than 40 years, with the number of patients treated each year growing as allograft quantity and quality increase. To date, the effects of postoperative management on outcomes after these procedures have received relatively little focus in the peer-reviewed literature. Hypothesis: Compliance with the recommended postoperative management protocol will be associated with significantly higher initial success and significantly lower revision and failure rates for patients undergoing osteochondral and/or meniscal allograft transplantation in the knee. Study Design: Cohort study; Level of evidence, 3. Methods: Patients were prospectively enrolled into a dedicated registry designed to follow outcomes after osteochondral and/or meniscal allograft transplantation. Patients were included when at least 1 year of follow-up data were available, including data on complications and reoperations, patient-reported outcome measures, compliance with rehabilitation, revisions, or failures, based on the electronic medical record and communication logs with patients' outpatient physical therapists. Results: For patients meeting the inclusion criteria (N = 162), compliance with the prescribed procedure-specific postoperative management protocol was associated with significantly higher 1- to 3-year success and significantly lower revision and failure rates. Specifically, patients who were compliant were 6.3 times less likely to need allograft revision or total knee arthroplasty and 7.5 times more likely to have a successful outcome at 1 to 3 years after osteochondral and/or meniscal allograft transplantation. In addition to noncompliance, older patient age and higher body mass index were associated with inferior short-term outcomes in this cohort. Conclusion: These data suggest that compliance with procedure-specific postoperative rehabilitation protocols is associated with higher success, lower revision, and lower failure rates for patients undergoing osteochondral and meniscal allograft transplantation. Given these results showing the importance of these modifiable risk factors, our center has devoted resources to preoperative patient assessment and communication to provide education, set appropriate expectations, identify and address modifiable risk factors, impediments, and noncompliance, and monitor and adjust postoperative care as indicated.